Hyperactivation of mTORC1 in a double hit mutant zebrafish model of tuberous sclerosis complex causes increased seizure susceptibility and neurodevelopmental abnormalities - De Meulemeester, Ann-Sofie; Heylen, Lise; Siekierska, Aleksandra; Mills, James D.; Romagnolo, Alessia; Van Der Wel, Nicole N.; Aronica, Eleonora; de Witte, Peter A. M. (Frontiers in Cell and Developmental Biology, 2022)
Tuberous sclerosis complex (TSC) is a multisystem genetic disorder caused by pathogenic variants in TSC1 and TSC2 genes. TSC patients present with seizures and brain abnormalities such as tubers and subependymal giant cells astrocytoma (SEGA). Despite common molecular and clinical features, the severity of the disease varies greatly, even intrafamilially. The second hit hypothesis suggests that an additional, inactivating mutation in the remaining functional allele causes a more severe phenotype and therefore explains the phenotypic variability. Recently, second hit mutations have been detected frequently in mTORopathies. To investigate the pathophysiological effects of second hit mutations, several mouse models have been developed. Here, we opted for a double mutant zebrafish model that carries a LOF mutation both in the tsc2 and the depdc5 gene. To the best of our knowledge, this is the first time a second-hit model has been studied in zebrafish. Significantly, the DEP domain-containing protein 5 (DEPDC5) gene has an important role in the regulation of mTORC1, and the combination of a germline TSC2 and somatic DEPDC5 mutation has been described in a TSC patient with intractable epilepsy. Our depdc5-/-x tsc2-/- double mutant zebrafish line displayed greatly increased levels of mammalian target of rapamycin (mTORC1) activity, augmented seizure susceptibility, and early lethality which could be rescued by rapamycin. Histological analysis of the brain revealed ventricular dilatation in the tsc2 and double homozygotes. RNA-sequencing showed a linear relation between the number of differentially expressed genes (DEGs) and the degree of mTORC1 hyperactivity. Enrichment analysis of their transcriptome revealed that many genes associated with neurological developmental processes were downregulated and mitochondrial genes were up-regulated. In particular, the transcriptome of human SEGA lesions overlapped strongly with the double homozygous zebrafish larvae. The data highlight the clinical relevance of the depdc5-/- x tsc2-/- double mutant zebrafish larvae that showed a more severe phenotype compared to the single mutants. Finally, analysis of gene-drug interactions identified interesting pharmacological targets for SEGA, underscoring the value of our small zebrafish vertebrate model for future drug discovery efforts.